Accumulation of the F plasmid TraJ protein in cpx mutants of Escherichia coli. - Silverman, P M (1993)
We report here studies of the cellular control of F plasmid TraJ protein levels, focusing on the effects of chromosomal cpx mutations. The principal conclusion from our results is that the cpx mutations impair accumulation of the TraJ protein, thereby reducing tra gene expression. We measured TraJ activity in vivo by expression of a traY'-'lacZ fusion gene and TraJ protein by immuno-overlay blot. In strains with normal TraJ levels, traY expression and donor-related functions were reduced in cells carrying any of four cpxA mutations. In the strain background used to isolate cpx mutants, these reductions were especially evident in cells grown to high density, when traY expression and donor activity both increased in cpx+ cells. In each of the four cpxA mutants tested, TraJ levels were lower than in the otherwise isogenic cpxA+ strain. In cells grown to high density, the differences ranged from 4-fold in the cpxA6 strain to > 10-fold in the cpxA2, cpxA5, and cpxA9 strains. The cpxA2 mutation had little or no effect on traY expression or on donor-related functions when TraJ was present in excess of its limiting level in F' or Hfr cells or on a mutant traY promoter whose expression in vivo was independent of TraJ.